Multidimensional nanomaterials for supercapacitors: Next generation energy storage - Verma S.; Verma S.; Kumar S.; Verma B. (My University, 2025)
Multidimensional Nanomaterials for Supercapacitors: Next Generation Energy Storage explores the cutting-edge advancements in multidimensional nanomaterials for supercapacitor applications, addressing key techniques, challenges, and future prospects in the field. The book offers a comprehensive overview of the fundamentals of supercapacitors, including electrode materials, electrolytes, charge storage mechanisms, and performance metrics. © 2024, Bentham Books imprint. All rights reserved.